EL ABSTENCIONISMO EN LAS ELECCIONES PRESIDENCIALES DE COSTA RICA (1953-2002) - Hernández Rodríguez, Óscar (2023)
The stability of abstention rates from 1962 to 1994 —around 18,9 %— ended in 1998 when the abstention rate jumped to 30 %, and registered 31,9 % in February 2002. The higher rate of 39,8 % in April lost importance because of the special nature of the second round and the attitude of many PAC supporters. Traditionally abstention rates have been higher in the provinces of Puntarenas and Limón, among electors in the 22-33 age group and especially among the age group ´70 or older’. Abstention rates in women were lower than those of men in age groups 18-21 to 38-41 in 1990, and to 58-61 in 1998. Abstainers tend to persist in that condition and the elections of 1994 and 1998 were no exception. Votes for PAC came from those who voted in 1998, not from abstainers. The abstention rate increase in 1998 was national and very uniform, suggesting common causes. One of them is the moral aspect.